Analysis on pixel number of elemental image in integral imaging 3D display - Deng, Huan; Luo, Cheng-Gao; Wu, Fei; Ji, Chao-Chao; Wang, Qiong-Hua (Optik (Stuttgart), 2017)
We analyze the effect of pixel number of elemental image on the resolution and depth of focus in depth-priority integral imaging display. By modeling the pupil as a thin lens, we simulate the retinal image received by an observer’s one eye in four situations according to the principle of geometrical optics. A subject test is carried out to find the minimal pixel number to maintain the resolution and depth of focus of 3D images. The experimental results show how the resolution and depth of focus are degraded as the decreasing of pixel number of elemental image. When the pixel number of elemental image is 36×36 or higher, high-quality 3D images could be produced by the integral imaging 3D display.